TOPCon battery and preparation method thereof
By printing and sintering the main grid and fine grids on the TOPCON batteries, the problem of the spread of the slurry to the passivation layer or the PN area is solved, and the conversion efficiency and yield of the battery are improved.
Patent Information
- Application Number
- CN202411526919.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-28
AI Technical Summary
During the preparation of TOPCon batteries, the slurry at the overlap between the main gate and the fine gate can easily diffuse to the passivation layer or the pn junction region during the sintering and laser-induced sintering, resulting in a decrease in battery efficiency and yield.
Use low -corrosive pulp printed main grids and fine grids on the positive and back of the TOPCON battery, and sintering and laser -induced sintering to control the grown composition and sintering temperature to avoid the spread of the slurry to the passivation layer or the PN association. Essence
Effectively avoid the diffusion of the slurry in the process of sintering and laser -induced sintering, improve the conversion efficiency and yield of the battery, and improve the opening voltage, filling factor and product yield.
Smart Images

Figure CN119384070A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of TOPCon batteries, and in particular to a TOPCon battery and a method for preparing the same. Background Art
[0002] TOPCon (Tunnel Oxide Passivated Contact) cells are TOPCon cells with tunnel oxide passivated contact based on the principle of selective carriers. N-type silicon is used as the cell substrate, and an ultra-thin silicon oxide layer is prepared on the back of the cell, and then a thin layer of doped silicon is deposited. The two together form a passivated contact structure, which can effectively reduce the surface recombination and metal contact recombination of carriers. After the introduction of laser induced sintering technology, the electrode slurry of TOPCon cells has also been improved accordingly. The front fine grid slurry uses a low-corrosion silver paste containing a trace amount of Al or no Al, the back fine grid also uses a low-corrosion silver paste, and the front and back main grid slurries also use low-corrosion silver paste to achieve the purpose of reducing metal damage. However, after adopting the above measures, the components at the overlap of the main and fine grids will diffuse with each other during the preparation of the electrode, causing damage or damage to the passivation layer and pn junction area of the cell, thereby reducing the efficiency and yield of the cell. Summary of the invention
[0003] The present application aims to solve one of the technical problems in the related art at least to a certain extent. To this end, one object of the present application is to provide a TOPCon battery and a preparation method thereof.
[0004] The first aspect of the present application provides a method for preparing a TOPCon battery, comprising the following operations: Providing a TOPCon cell, and printing a main grid on the back of the TOPCon cell using a first low-corrosion slurry and drying the main grid; Printing a fine grid on the back of the TOPCon cell using the first slurry and drying the fine grid; Printing a main grid on the front side of the TOPCon cell using a second low-corrosion slurry and drying the main grid; Using the second slurry to print fine grids on the front side of the TOPCon cell and drying the grids; Sintering the TOPCon cell after printing, and then laser-induced sintering the front fine grid of the TOPCon cell; The first low-corrosion slurry and the second low-corrosion slurry independently include the following components: 82wt%~94wt% silver powder, 0.4wt%~3wt% first glass powder, and 5wt%~15wt% organic vehicle; The first glass powder includes SiO2, PbO, Bi2O3, CuO and MnO. Based on the first glass powder, the total weight percentage of PbO, Bi2O3, CuO and MnO is less than 50wt%.
[0005] The first aspect of the present application can prevent the slurry at the junction of the main grid and the fine grid from diffusing into the passivation layer or the pn junction region during sintering and laser induced sintering to form a new slurry corrosion system, thereby destroying or damaging the passivation layer and the pn junction region of the cell. Furthermore, the first aspect of the present application can improve the conversion efficiency and yield of the cell.
[0006] The second aspect of the present application provides a TOPCon battery prepared in the first aspect. The open circuit voltage, fill factor, conversion efficiency and product yield of the TOPCon battery in the second aspect are improved to varying degrees.
[0007] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which: Figure 1 This is a cross-sectional view of a TOPCon battery; Figure 2 This is a top view of the TOPCon battery.
[0009] Reference numerals: 1-N-type silicon wafer; 2-p + Emitter; 3-passivation layer; 4-front anti-reflection film; 5-front main grid; 6-front fine grid; 7-tunneling layer; 8-Poly layer; 9-back anti-reflection film; 10-back main grid; 11-back fine grid; 12-welding point. DETAILED DESCRIPTION
[0010] Embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, and should not be construed as limiting the present application.
[0011] Glossary: The first low corrosion slurry, also known as back main grid slurry, is used to form the main grid on the back side of the battery.
[0012] The first slurry, also called back side fine grid slurry, is used to form fine grids on the back side of the battery.
[0013] The second low corrosion slurry, also known as the front main grid slurry, is used to form the main grid on the front side of the battery.
[0014] The second slurry, also called front fine grid slurry, is used to form fine grids on the front side of the battery.
[0015] See also Figure 1 and Figure 2 , Figure 1 and Figure 2 The TOPCon cell is a cross-sectional view and a top view respectively. The TOPCon cell comprises an N-type silicon wafer 1. The front side of the N-type silicon wafer 1 is sequentially stacked with p-type silicon wafers in a direction away from the front side. + The back side of the N-type silicon wafer 1 is stacked with a tunneling layer 7, a Poly layer 8, a back side anti-reflection film 9 and a back side gate line in sequence from the back side to the direction away from the back side; wherein the front side gate line includes a front side main gate 5 and a front side fine gate 6, and the back side gate line includes a back side main gate 10 and a back side fine gate 11; see Figure 2 It can be seen that the front main grid 5 and the front fine grid 6 form an overlap at the intersection, and some of the overlaps also serve as welding points 12. The structure of the back main grid 10 and the back fine grid 11 is the same as that of the front, and will not be repeated here.
[0016] Accordingly, in the first aspect of the present application, a method for preparing a TOPCon battery is proposed.
[0017] In some embodiments, the method for preparing the TOPCon battery comprises the following operations: S1. Provide a TOPCon cell, use a first low-corrosion slurry to print a main grid on the back of the TOPCon cell, and dry it; S2, using the first slurry to print fine grids on the back of the TOPCon cell and drying; S3, using a second low-corrosion slurry to print a main grid on the front side of the TOPCon cell and drying it; S4, using the second slurry to print fine grids on the front side of the TOPCon cell and drying; S5, sintering the TOPCon cell after printing, and then laser-induced sintering the front fine grid of the TOPCon cell; the TOPCon cell after printing refers to the TOPCon cell after completing steps S1 to S4; The first low-corrosion slurry and the second low-corrosion slurry independently include the following components: 82wt%~94wt% silver powder, 0.4wt%~3wt% first glass powder, and 5wt%~15wt% organic vehicle; The first glass powder includes SiO2, PbO, Bi2O3, CuO and MnO. Based on the first glass powder, the total weight percentage of PbO, Bi2O3, CuO and MnO is less than 50wt%.
[0018] In the first aspect of the present application, after the front main grid and fine grid, the back main grid and fine grid are sintered, the slurry of the main grid and the slurry of the fine grid are melted and solidified respectively, and the front main grid and the back main grid have formed good electrodes at this time, and the front fine grid cannot be combined with the p during the sintering process. + The emitter forms a good contact, so it is repaired by laser induced sintering; during the laser induced sintering process, the slurry at the overlap of the front main grid and the front fine grid will melt and diffuse again. Since the total weight percentage of the corrosive metals of PbO, Bi2O3, CuO and MnO in the first etching slurry of the front main grid is less than 50wt%, when it is in a molten state with the front fine grid slurry (second slurry), the elements at the overlap can only undergo weak thermal diffusion or no diffusion, thereby reducing the damage to the lower pn junction. In addition, during the laser induced sintering process, the front fine grid slurry and p + The material at the interface of the emitter contact reacts and diffuses to the cold zone under the high temperature conditions created by laser induced sintering, forming Ag-Si alloy or Ag-Si-Al alloy (when the first slurry contains aluminum) at the interface, which is the contact point formed by laser induced sintering. + The emitter forms a good ohmic contact. The first aspect of the present application can prevent the slurry at the junction of the main grid and the fine grid from diffusing to the passivation layer or the pn junction area during sintering and laser induced sintering to form a new slurry corrosion system, causing damage or destruction to the passivation layer and the pn junction area of the battery cell, thereby reducing the efficiency and yield of the battery.
[0019] Further, the first low corrosion slurry includes the following components: 82wt%~94wt% silver powder, for example, 82wt%, 90wt% silver powder, 94wt% silver powder, etc.; 0.4wt%~3wt% first glass powder, for example, 0.4wt%, 1wt%, 2wt%, 3wt%, etc.; 5wt%~15wt% organic vehicle, for example, 5wt%, 10wt%, 15wt%, etc. Further, based on the first glass powder, the first glass powder includes SiO2, PbO, Bi2O3, CuO and MnO, and the total weight percentage of PbO, Bi2O3, CuO and MnO is less than 50wt%, for example, 50wt%, 40wt%, 30wt%, 20wt%, etc., and correspondingly, the weight percentage of SiO2 is 50wt%, 60wt%, 70wt%, 80wt%, etc. The components of the second low corrosion slurry are similar to those of the first low corrosion slurry, and will not be repeated here.
[0020] In the present application, low-corrosion slurry refers to a silver paste for preparing gate lines in which the Al content in the slurry is below 3 wt %.
[0021] In some embodiments, in the preparation method of the TOPCon battery, the sintering temperature in S5 is: 650°C to 800°C, for example, 650°C, 700°C, 730°C, 740°C, 800°C, etc. The sintering temperature range is more than 20°C lower than the sintering peak value of normal mass production in the industry, so that the main grids on the front and back sides have good current transmission and reliability after sintering, while ensuring that the fine grids on the back side can form good contact. In addition, this sintering plays a role in pre-sintering the fine grids on the front side, and the fine grid slurry on the front side is initially melted during the sintering process to form some contact points; during this sintering process, the slurry components at the overlap of the front / back main / fine grids do not undergo mutual thermal diffusion or only undergo mutual weak diffusion. Further, the sintering time may include 10s to 300s, for example, 10s, 50s, 100s, 300s, etc. Thus, the sintering is completed quickly.
[0022] Laser induced sintering technicians can select according to their needs. The selection principles are as follows: the operating parameters of the laser induced equipment are different according to the type of the corresponding front fine grid slurry, and the power can be divided into low power (below 1000W), medium power (1000~3000W) and high power (above 3000W); the laser type can be divided into continuous laser and pulsed laser according to the working type, among which the continuous laser can output continuously for a long period of time, with stable operation and high thermal effect; the pulsed laser outputs in the form of pulses, and its main characteristics are high peak power and small thermal effect; according to the pulse time length, the pulsed laser can be further divided into milliseconds, microseconds, nanoseconds, picoseconds and femtoseconds. Generally speaking, the shorter the pulse time, the higher the single pulse energy, the narrower the pulse width, and the higher the processing accuracy. The laser type can be divided into infrared lasers, visible light lasers, ultraviolet lasers, etc. according to the output wavelength. Different structures of materials can absorb different wavelength ranges of light. For example, metals have a higher absorption rate for near-infrared light, and non-metals have better absorption of the wavelength (10.6 μm) emitted by CO2 lasers. During the laser induced sintering process, the paste components at the main / fine grid overlap do not undergo mutual thermal diffusion or only undergo weak mutual diffusion, so that the main / fine grid overlap can not cause metal corrosion to the passivation layer, or no metal corrosion occurs, thereby reducing the metal composite and metal corrosion damage at the overlap, while reducing the contact resistance at the overlap, thereby improving the battery's fill factor (FF), open circuit voltage (Voc) and conversion efficiency. At the same time, it also reduces the product degradation rate caused by large metal damage and composite at the overlap. As some examples, in the preparation method of the TOPCon battery, the laser induced sintering in S5 adopts the line scanning mode of a continuous laser, and the laser induced sintering includes the following operations: the bias voltage is 10V~30V, for example, it can be 10V, 20V, 30V, etc.; the laser spot width is 10 μm, 40 μm, 60 μm, 150 μm, etc.; the current is 1 A~15 A, for example, 1 A, 6 A, 11 A, 15 A, etc.; the laser power is 10W~60W, for example, it can be 10W, 25W, 50W, 60W, etc.; the laser scanning speed is 0.1 m / s~80m / s, for example, it can be 0.1 m / s, 0.1 m / s, 1 m / s, 20 m / s, 45 m / s, 80 m / s, etc. Thus, the front fine grid and p + The emitter forms a good ohmic contact.
[0023] The first paste and the second paste in the present application can adopt all the disclosed silver pastes for preparing gate line electrodes. Preferably, the components of the first slurry include: 80wt%~93wt% silver powder, for example, 80wt%, 83wt%, 87wt%, 93wt%, etc.; 0.5wt%~2wt% second glass powder, for example, 0.5wt%, 1wt%, 1.5wt%, 2wt%, etc.; 6wt%~18wt% organic carrier, for example, 6wt%, 10wt%, 15wt%, 18wt%, etc.; based on the second glass powder, the second glass powder includes 50wt%~70wt% TeO2, 30wt%~40wt% SiO2 and less than 10wt% PdO; for example, 50wt% TeO2, 60wt% TeO2, 70wt% TeO2, etc.; 30wt% SiO2, 40wt% SiO2, 50wt% SiO2, etc.; 10wt% PdO, 5wt% PdO, 2wt% PdO, 0wt% PdO, etc. As a result, the slurry of this system can form a good ohmic contact with the doped polysilicon layer on the back of the battery, while causing less damage to the back passivation layer. Preferably, the components of the second slurry include: 80wt%~93wt% silver powder, 0.5wt%~2wt% third glass powder, 6wt%~18wt% organic carrier; for example, the silver powder can be 80wt%, 83wt%, 87wt%, 93wt%, etc.; the third glass powder can be 0.5wt%, 1wt%, 1.5wt%, 2wt%, etc.; the organic carrier can be 6wt%, 10wt%, 15wt%, 18wt%, etc. Further, based on the third glass powder, the third glass powder includes 50wt%~70wt% PbO and 30wt%~50wt% BaO. For example, 50wt%, 60wt%, 65wt%, 70wt%, etc. of PbO; 30wt%, 40wt%, 50wt%, etc. of BaO. Therefore, it is suitable for laser induced sintering process, and the damage to the front passivation layer and pn layer will be greatly reduced due to the absence of Al.
[0024] In some embodiments, the sizes of the silver powders of the first low-corrosion slurry, the second low-corrosion slurry, the first slurry, and the second slurry in the preparation method of the TOPCon battery are independently 0.5 μm to 3 μm, for example, the sizes of the silver powders of the first low-corrosion slurry, the second low-corrosion slurry, the first slurry, and the second slurry are all 0.5 μm to 3 μm, but the median sizes are different. The present application uses laser particle size analysis to measure the size of the silver powder. The size of the silver powder is small and distributed in multiple particle sizes. During the sintering process, the multiple particle sizes cooperate with each other to improve the density of the sintering.
[0025] In some embodiments, the viscosity of the first low-corrosion slurry and the second low-corrosion slurry in the preparation method of the TOPCon battery is independently 15 Pa.s to 35 Pa.s, for example, 15 Pa.s, 20 Pa.s, 35 Pa.s, etc. As a result, the slurry has good printability, good aspect ratio (good grid line shaping), and the formed grid line has good current transmission and collection capabilities and good welding performance.
[0026] In some embodiments, the viscosity of the first slurry and the second slurry in the preparation method of the TOPCon battery is independently 20 Pa.s to 150 Pa.s, for example, 20 Pa.s, 50 Pa.s, 120 Pa.s, 150 Pa.s, etc. As a result, the slurry has good printability, good aspect ratio (good grid line shaping), and the formed grid line has good current transmission capability. The viscosity data of this application are all obtained by testing under the test standard of ASTM D1084.
[0027] In the field of silver paste, the organic carrier may include a solvent, and may also include additives such as a thickener and a dispersant, a wetting agent, and a thixotropic agent. In some embodiments, the organic carriers of the first low-corrosion paste, the second low-corrosion paste, the first paste, and the second paste independently include at least one of butyl carbitol acetate, alcohol ester dodeca (CAS: 25265-77-4), and butyl carbitol (CAS: 112-34-5).
[0028] In some embodiments, the TOPCon cell manufacturing method adopts a TOPCon cell, comprising an N-type silicon wafer, wherein the N-type silicon wafer has a front side and a back side; the front side of the N-type silicon wafer is sequentially stacked with p + The back side of the N-type silicon wafer is stacked with a tunneling layer, a Poly layer and a back side anti-reflection film in sequence from the back side to the direction away from the back side. Specifically, the TOPCon cell satisfies at least one of the following characteristics: a. The tunneling layer includes a silicon oxide layer; b. The thickness of the tunneling layer is 1nm to 3nm; c. The Poly layer includes a phosphorus-doped polysilicon layer; d. The thickness of the Poly layer is 20nm to 220nm; e. The square resistance of the Poly layer is 30Ω / □ to 90Ω / □; f. The passivation layer includes AlO xg. The thickness of the passivation layer is 2nm~20nm; h. The front anti-reflection film and the back anti-reflection film independently include at least one of a silicon nitride film, a silicon oxynitride film, and a silicon oxide film; i. The thickness of the front anti-reflection film and the thickness of the back anti-reflection film independently range from 40 nm to 100 nm. Thus, the comprehensive performance of the TOPCon cell is optimized.
[0029] The second aspect of the present application provides a TOPCon battery, which is prepared according to the preparation method described in the first aspect. As a result, the sintering process and slurry are optimized, the metal damage of the emitter and the pn junction is reduced, and the open circuit voltage, fill factor, conversion efficiency and product yield of the battery are improved to varying degrees.
[0030] The present application is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present application in any way.
[0031] Example 1 (1) Cleaning and texturing of N-type single crystal silicon wafers with a thickness of 130 μm; (2) Boron diffusion and oxidation process are performed on the front side of the N-type single crystal silicon wafer to prepare p + An emitter, wherein after boron diffusion, a diffusion square resistance of 160 Ω / □ is obtained, and after oxidation, an oxidation square resistance of 280 Ω / □ is obtained; (3) Clean the back side of the N-type single crystal silicon wafer to remove BSG (borosilicate glass); (4) Oxidize the back of the N-type single crystal silicon wafer and deposit n + Polysilicon, obtaining a Poly layer with a thickness of 70 nm; (5) In p + AlO deposition on emitter x Passivation film, thickness 10 nm; (6) A 50 nm thick silicon nitride film is deposited on the front side as a front anti-reflection film; a 50 nm thick silicon nitride film is deposited on the back side as a back anti-reflection film to obtain a TOPCon cell; (7) Screen-printing the main grid on the back of the TOPCon cell using the first low-corrosion slurry and drying it; Using the first slurry, screen-printing a fine grid on the back of the TOPCon cell and drying it; The second lowest corrosion slurry is used to screen print the main grid on the front side of the TOPCon cell and then dried; The second slurry is used to screen print a fine grid on the front side of the TOPCon cell and then dried; The components of the first low-corrosion slurry and the second low-corrosion slurry are shown in Table 1. The viscosity of the first low-corrosion slurry was measured to be 20 Pa.s, and the viscosity of the second low-corrosion slurry was measured to be 23 Pa.s.
[0032] The components of the first slurry are: 90wt% silver powder, 1wt% TeO2, 0.8wt% SiO2, 0.2wt% PbO, 8wt% butyl carbitol acetate; the measured viscosity is 24 Pa.s.
[0033] The components of the second slurry are: 93 wt % silver powder, 6 wt % butyl carbitol acetate, 3.5 wt % PbO and 3.5 wt % BaO; the measured viscosity is 25 Pa.s.
[0034] The silver powder size distribution in the first low-corrosion slurry, the second low-corrosion slurry, the first slurry and the second slurry is 0.5 μm to 3 μm.
[0035] (7) Sinter the dried TOPCon cell at 650°C for 100 s; (8) Laser induced sintering of the front fine grid was used. The specific operation was as follows: the line scanning mode of the continuous laser was used, the applied bias voltage was 10 V, the laser spot width was 30 μm, the current was 15 A, the laser power was 10 W, and the laser scanning speed was 5 m / s.
[0036] Embodiment 2 to Embodiment 3 The other operations are the same as those in Example 1, except that the components of the first low-corrosion slurry and the second low-corrosion slurry in step (6), and the process conditions of steps (7) and (8) are specifically shown in Table 1.
[0037] Embodiment 4 to Embodiment 5 The other operations are the same as those in Example 2, except that the process conditions of step (7) are shown in Table 1.
[0038] Comparative Example 1 The rest is the same as Example 2, except that the components of the first low-corrosion slurry in step (6) are specifically shown in Table 1.
[0039] Comparative Example 2 The rest is the same as Example 2, except that the components of the second low-corrosion slurry in step (6) are specifically shown in Table 1.
[0040] Comparative Example 3 The rest is the same as Example 2, except that the components of the first low-corrosion slurry and the components of the second low-corrosion slurry in step (6) are specifically shown in Table 1.
[0041] Table 1
[0042] Table 1
[0043] Note: In Table 1, M1 is the weight percentage of PbO, Bi2O3, CuO and MnO in the second glass powder of the first low-corrosion slurry; M2 is the weight percentage of PbO, Bi2O3, CuO and MnO in the third glass powder of the second low-corrosion slurry.
[0044] Table 1
[0045] Test analysis The TOPCon batteries of Examples 1 to 4 and Comparative Examples 1 to 3 were subjected to IV tests. The IV tests were performed in accordance with the third edition of IEC.60904-9.2020, and the data obtained are shown in Table 2. In addition, the product yield is judged based on the conversion efficiency of the TOPCon battery and whether the EL black line (the line with obvious differences caused by cracks under the EL test) is defective. The TOPCon battery can only be judged as a good product if it simultaneously satisfies the conversion efficiency being greater than 25.1% and having no EL black line defect. Otherwise, it is a defective product. The product yield in Table 2 is the product yield obtained by counting 500,000 TOPCon batteries.
[0046] Table 2
[0047] It can be seen from Table 2 that the glass powder of the first and second low-corrosion slurries described in Examples 1 to 5 is the glass powder of the present application, and the proportion of PbO, Bi2O3, CuO, and MnO in the glass powder is ≤50%; wherein the sintering peak temperature adopted in Examples 1 to 4 is between 650°C and 800°C, which can obtain better battery conversion efficiency and product yield; the sintering peak temperature adopted in Example 5 reaches 850°C. Due to the excessively high sintering peak temperature, the front and back fine grid slurries cause metal damage to the front and back passivation layers and the pn junction, and the open circuit voltage (Voc) and fill factor (FF) of the battery are both reduced, and the battery efficiency is lower than that of Examples 1 to 4. At the same time, the product yield caused by the inefficiency is also reduced accordingly.
[0048] In comparative example 1, the proportion of PbO, Bi2O3, CuO and MnO in the glass powder of the second low corrosion slurry is ≤50%, while the proportion of PbO, Bi2O3, CuO and MnO in the glass powder of the first low corrosion slurry is >50%, which results in the mutual thermal diffusion of components between the back main grid slurry and the back fine grid slurry at the overlap during sintering and laser induced sintering. The metal composite at the overlap is increased, the metal corrosion ability is enhanced, and the back passivation layer and even the inner tunneling layer are damaged, the Voc of the battery is reduced, the FF is reduced, the conversion efficiency is reduced, and the product yield is reduced.
[0049] In comparative example 2, the proportion of PbO, Bi2O3, CuO and MnO in the glass powder of the first low-corrosion slurry is ≤50%, and the proportion of PbO, Bi2O3, CuO and MnO in the glass powder of the second low-corrosion slurry is >50%. This results in thermal diffusion of components between the front main grid slurry and the front fine grid slurry at the overlap during the sintering process and laser induced sintering, increased metal composite at the overlap, stronger metal corrosion ability, damage to the front passivation layer and even the internal pn junction area, reduced Voc of the battery, reduced FF, reduced conversion efficiency, and at the same time reduced product yield.
[0050] In the glass powder of the first and second low-corrosion slurries described in Comparative Example 3, the proportions of PbO, Bi2O3, CuO, and MnO in the glass powder are all greater than 50%, which results in a mutual thermal diffusion of the components of the back main grid slurry and the back fine grid slurry at the overlap during the pre-sintering process, increasing the metal composite at the overlap, and strengthening the metal corrosion ability, causing damage to the back passivation layer and even the inner tunneling layer; at the same time, the front main grid slurry and the front fine grid slurry at the overlap during the pre-sintering process, increasing the metal composite at the overlap, and strengthening the metal corrosion ability, causing damage to the front passivation layer and even the inner pn junction area, causing a greater reduction in the Voc of the battery, a greater reduction in FF, a greater decrease in conversion efficiency, and a greater reduction in product yield.
[0051] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0052] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A method for preparing a TOPCon battery, characterized in that: The following operations are included: Providing a TOPCon cell, and printing a main grid on the back of the TOPCon cell using a first low-corrosion slurry and drying the main grid; Printing a fine grid on the back of the TOPCon cell using the first slurry and drying the fine grid; Printing a main grid on the front side of the TOPCon cell using a second low-corrosion slurry and drying the main grid; Using the second slurry to print fine grids on the front side of the TOPCon cell and drying the grids; Sintering the TOPCon cell after printing, and then laser-induced sintering the front fine grid of the TOPCon cell; The first low-corrosion slurry and the second low-corrosion slurry independently include the following components: 82wt%~94wt% silver powder, 0.4wt%~3wt% first glass powder, and 5wt%~15wt% organic vehicle; The first glass powder includes SiO2, PbO, Bi2O3, CuO and MnO. Based on the first glass powder, the total weight percentage of PbO, Bi2O3, CuO and MnO is less than 50wt%.
2. The method for preparing a TOPCon battery according to claim 1, characterized in that: The first low-corrosion slurry and the second low-corrosion slurry each independently satisfy at least one of the following characteristics: The size of the silver powder is 0.5 μm to 3 μm; The viscosity is 15 Pa.s~35 Pa.s.
3. The method for preparing a TOPCon battery according to claim 1, characterized in that: The sintering conditions include: 650°C to 800°C; and / or The sintering time ranges from 10s to 300s.
4. The method for preparing a TOPCon battery according to claim 1, characterized in that: The laser induced sintering adopts a line scanning mode, with a bias voltage of 10V~30V, a laser spot width of 10 μm~150 μm, a current of 1 A~15 A, a laser power of 10W~60W, and a laser scanning speed of 0.1 m / s~80 m / s.
5. The method for preparing a TOPCon battery according to claim 1, characterized in that: The components of the first slurry include: 80wt%~93wt% silver powder, 0.5wt%~2wt% second glass powder, and 6wt%~18wt% organic vehicle; Taking the second glass powder as a reference, the second glass powder includes 50wt% to 70wt% TeO2, 30wt% to 40wt% SiO2 and less than 10wt% PdO.
6. The method for preparing a TOPCon battery according to claim 1, characterized in that: The components of the second slurry include: 80wt%~93wt% silver powder, 0.5wt%~2wt% third glass powder, and 6wt%~18wt% organic vehicle; Based on the third glass powder, the third glass powder includes 50 wt % to 70 wt % of PbO and 30 wt % to 50 wt % of BaO.
7. The method for preparing a TOPCon battery according to claim 5 or 6, characterized in that: The first slurry and the second slurry each independently satisfy at least one of the following characteristics: The size of the silver powder is 0.5 μm to 3 μm; The viscosity is 20 Pa.s~150 Pa.s.
8. The method for preparing a TOPCon battery according to any one of claims 1 to 6, characterized in that: The organic carrier includes at least one of butyl carbitol acetate, alcohol ester dodecaned, and butyl carbitol.
9. The method for preparing a TOPCon battery according to any one of claims 1 to 6, characterized in that: The TOPCon cell comprises an N-type silicon wafer, and the N-type silicon wafer has a front side and a back side; The front side of the N-type silicon wafer is stacked with p-type silicon wafers in a direction away from the front side. + An emitter, a passivation layer and a front anti-reflection film, the back side of the N-type silicon wafer is sequentially stacked with a tunneling layer, a Poly layer and a back anti-reflection film in a direction away from the back side.
10. The method for preparing a TOPCon battery according to claim 9, characterized in that: The TOPCon cell satisfies at least one of the following characteristics: a. The tunneling layer includes a silicon oxide layer; b. The thickness of the tunneling layer is 1 nm to 3 nm; c. The Poly layer includes a phosphorus-doped polysilicon layer; d. The thickness of the Poly layer is 20nm~220nm; e. The sheet resistance of the Poly layer is 30Ω / □~90Ω / □; f. The passivation layer includes AlO x layer; g. The thickness of the passivation layer is 2nm~20nm; h. The front anti-reflection film and the back anti-reflection film independently include at least one of a silicon nitride film, a silicon oxynitride film, and a silicon oxide film; i. The thickness of the front anti-reflection film and the thickness of the back anti-reflection film are independently 40 nm to 100 nm.
11. A TOPCon battery obtained according to the preparation method according to any one of claims 1 to 10.